Individualistic Vikings: Culture, Economics and Iceland - Mixa, Már Wolfgang; Vaiman, Vlad (Stjórnsýslustofnun, 2015)
Icelandic culture has generally been considered to share many similarities to the Nordic cultures. However, the financial crisis in 2008 painted a completely different picture, with the Nordic nations faring much less worse than Iceland, which saw its banking system becoming almost entirely worthless. Looking at traditional cultural yardsticks in the vein of the most commonly used research in the field of business and organizational management, generally linked to Hofstede´s dimensional studies, one would at first glance conclude that Icelanders would have behaved in a similar manner as people in the Nordic nations. By focusing on savings ratio, it is shown that Icelanders were much more risk-seeking during the prelude of the crisis. Many nations badly hit during the 2008 financial crisis have a high level of individualism inherent in their culture. Iceland fits this scenario. Thus while general cultural characteristics may lack explanatory power regarding economic behavior of people between cultures, the individual/collective cultural dimension may provide clues of what dangers (and possible strengths) lurk within societies from a financial point of view. Such developments may affect the financial stability of nations, especially those with a high level of individualism where financial liberalization with possible abuses is occurring.